Physical changes and pedestrian dynamics in public space: The Beşiktaş case - Turken, Araf Oyku (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2026)
Urban squares are crucial for urban life, enhancing city attractiveness and livability; nevertheless, many in Istanbul lack pedestrian-oriented design and sufficient infrastructure. Relatedly, several projects have been implemented in urban squares to overcome these issues. However, designing urban squares leads to both improvements and controversies, reshaping not only the physical environment but also how individuals engage with public space, and understanding pre/post dynamics of interventions provides comprehensive feedback and helps municipalities to resolve further needs. This study explores the impact of spatial changes on pedestrian behavior in Besiktas Barbaros Square (Istanbul/Turkey) and its surroundings. With a three-stage methodology, this research first identifies physical transformations by analyzing satellite imagery, street views, and field studies. Second, pedestrian flows and stationary activities are observed via manual video recordings (10 minutes, weekday/ weekend, 2022-2024), capturing the site both before (once the steel overpass was removed and before the site was redeveloped) and after interventions. These observations are mapped and analyzed using QGIS. Third, perspectives from professionals (n=31) in spatial fields -urban planners, architects, and landscape architects- are gathered through surveys and openended responses. The findings focused on the eastern part of the square due to observational constraints, which reveal that adding urban furniture impacts dynamic/stationary activities and enhanced social interactions. The new eagle sculpture also emerged as a focal point. According to professionals' evaluations, interventions contributed to partial improvements in several aspects between pedestrians and the space. However, considering location-based potentials, green space use and the spatial connection with the urban coastline still need to be improved.
Keywords: Behavior mapping; Besiktas; pedestrian behavior; public space; urban square; Architecture